VALIDATING AND EXPANDING THE HAWTHORNE STUDIES: EVIDENCE FROM INDONESIAN PUBLIC EMPLOYEES - Ariutama, I Gede Agus (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
Since Hawthorne study deconstructed Taylor’s time and motion studies, scholars of organization studies have shifted their attentions to human relations in the workplaces. The major implication is that employees’ relationship with supervisors as well as their peers, and their participation in decision-making process determine productivity. Although the Hawthorne experiments were conducted in the private sector, scholars of public administration believe that the implication from the experiment can be applied to the public sector as well. However, current discussion on the public-private distinction leads to an important research question: can lessons from the Hawthorne study apply to public organizations? The purpose of this study is to validate and expand the original Hawthorne studies and Jung and Lee (forthcoming) conducted in the public organizations by analyzing a large sample of Indonesian public officials. Findings suggest that physical conditions have no or weak impacts on self-assessed and client-evaluated work performance while human relations show positive effects. For the supervisor-assessed performance, participation and physical conditions are the significant predictors. This study gives a unique opportunity since this study investigates the Hawthorne effects in the Asian context for the first time.